DETERMINAN PENANAMAN MODAL ASING LANGSUNG DI ASEAN - Joko Susanto (Jurnal Riset Manajemen dan Bisnis, 2012)
ABSTRACT This research analysis the factors’ that determine the foreign direct investment (FDI) in ASEAN’s countries especially Indonesia, Malaysia, Philippine and Thailand during 1990-2009. Multinational Enterprises’ (MNE) must decide to choose a location for relocating its’ factory by market seeking dan resources seeking strategy. Based on this statement, it can be obtained the regression equation with foreign direct investment is a function of market size, worker’s productivity and infrastructure of road. Statistical data of UNESCAP was used in this research. The regression was base on the panel data model, while the estimation was based on common effects model. This results show that the market size, worker’s productivity and availability of infrastructure road could be an importance consideration for MNE’s in their choice for FDI. Keywords: foreign direct investment, market size, worker’s productivity, infrastructure of road